Human ageing as a catalyst for managementand its teaching (2006)
This article proposes several original ways through which acknowledgement of and awareness towards human ageing can be used to promote positive changes in management and its teaching, by means of sensibilization and recognition. The introduction and justification of this issue, is followed by the examination of relevant definitions and meaningful trends. Afterwards, some critics to management are discussed alongside the corresponding contributions derived from human ageing. Particularly, ideas are proposed to neutralize administrative fads, to humanize organizations, and to introduce more freedom. Finally, some specific applications are directed to enrich the field of management education with the potential offered by the elders.